Phosphate-solubilizing bacteria-mediated rock phosphate utilization with poultry manure enhances soil nutrient dynamics and maize growth in semi-arid soil - Kashif Khan (2978691) (2025)
Nutrient deficiencies in semi-arid soils limit crop productivity and degrade soil health. This study evaluated the combined effects of rock phosphate (RP), poultry manure (PM), and phosphate-solubilizing bacteria (PSB) on soil nutrient dynamics and maize performance under field conditions. A factorial randomized complete block design with three replications was employed. Changes in soil properties, including pH, electrical conductivity (EC), soil organic matter (SOM), and nutrient dynamics, were assessed. The integration of RP and PM, particularly with PSB inoculation, significantly (p < 0.05) improved soil and plant nitrogen (N), phosphorus (P), and potassium (K) levels. The most pronounced improvements were in the treatment with 90-RP + 6-PM + PSB, which increased soil total N by 285%, available P by 79%, and available K by 51%. Plant total N, P, and K were enhanced by 53, 419, and 50%, respectively. Similarly, nutrient uptake improved, with N uptake increasing by 142%, P by 283%, and K by 149.6%. This treatment also increased soil EC and SOM by 43% and 77%, respectively, while soil pH decreased by 3.23%. Consequently, maize grain yield, biological yield, 1,000-grain weight, and plant height were increased by 9.5, 13.8, 263.3, and 42%, compared to the control. Principal component analysis and Pearson’s correlation analysis revealed strong positive relationships between soil and plant nutrient parameters, except for soil pH, which was negatively correlated. Overall, RP, PM, and PSB present a sustainable, scalable, and environmentally friendly strategy to enhance soil fertility and maize productivity in nutrient-deficient semi-arid soils. Other Information Published in: Open Agriculture License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1515/opag-2025-0450